Determination of Managerial Ownership, Firm Size, and Profitability on Firm Value Jakarta Islamic Index - Subhan Aziz; Andi Surya; Hasbullah Hasbullah; Maria Septijantini Alie; Megasari Megasari (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study aims to analyze the influence of Managerial Ownership (MOWN), Firm Size (SIZE), and profitability (ROA) on Firm Value (EPS) of companies listed in the Jakarta Islamic Index (JII) on the Indonesia Stock Exchange during the 2019–2024 period. Methodology/approach: The research was conducted on 30 companies included in the JII, with purposive sampling used to select eight companies observed over six years, resulting in 48 research samples. This study applied a quantitative research method using data collected from annual financial reports. The analysis was performed using multiple linear regression with the SPSS software. Results/findings: The findings show that Managerial Ownership (MOWN) has a positive and significant effect on Firm Value (EPS), Firm Size (SIZE) has no significant effect, and profitability (ROA) has a positive and significant effect. Simultaneously, MOWN, SIZE, and ROA have a positive and significant effect on Firm Value (EPS). Conclusions: The results indicate that managerial ownership and profitability are the most important factors to consider for improving EPS, whereas firm size does not significantly determine firm value. Limitations: This study is limited to companies listed in the Jakarta Islamic Index (JII) during the 2019–2024 period, which may reduce the generalizability of the findings to other sectors or indices. Contribution: This study contributes to financial management studies by providing empirical evidence of the role of ownership structure and profitability in shaping firm value. This study is useful for investors, policymakers, and academics focusing on Islamic capital markets and corporate governance.